Influence of olive cake dietary supplementation on fecal microbiota of dairy cows - Russo, Nunziatina; Floridia, Viviana; D’Alessandro, Enrico; Lopreiato, Vincenzo; Pino, Alessandra; Chiofalo, Vincenzo; Caggia, Cinzia; Liotta, Luigi; Randazzo, Cinzia Lucia (Frontiers in Microbiology, 2023)
Olive by-products represent a valuable low-price feed supplement for animal nutrition. In the present study, the effect of the dietary destoned olive cake supplementation, on both composition and dynamics of the fecal bacterial biota of cow, was assessed by Illumina MiSeq analysis of the 16S rRNA gene. In addition, metabolic pathways were predicted by using the PICRUSt2 bioinformatic tool. Eighteen lactating cows, according to the body condition score, the days from calving, and the daily milk production were homogeneously allocated into two groups, control or experimental, and subjected to different dietary treatments. In detail, the experimental diet contained, along with the components of the control one, 8% of destoned olive cake. Metagenomics data revealed significant differences in abundance rather than in richness between the two groups. Results showed that Bacteroidota and Firmicutes were identified as the dominant phyla, accounting for over 90% of the total bacterial population. The Desulfobacterota phylum, able to reduce sulphur compounds, was detected only in fecal samples of cows allocated to the experimental diet whereas the Elusimicrobiota phylum, a common endosymbiont or ectosymbiont of various flagellated protists, was detected only in cows subjected to the control diet. In addition, both Oscillospiraceae and Ruminococcaceae families were found only in the experimental group whereas fecal samples of control cows showed the presence of Rikenellaceae and Bacteroidaceae families, usually associated with the high roughage or low concentrate diet. Based on the PICRUSt2 bioinformatic tool, pathways related to carbohydrate, fatty acid, lipid, and amino acids biosynthesis were mainly up regulated in the experimental group. On the contrary, in the control group, the metabolic pathways detected with the highest occurrence were associated with amino acids biosynthesis and degradation, aromatic compounds degradation, nucleosides and nucleotides biosynthesis. Hence, the present study confirms that the destoned olive cake is a valuable feed supplement able to modulate the fecal microbiota of cows. Further studies will be conducted in order to deepen the inter-relationships between the GIT microbiota and the host.